Incidence and survival of interstitial lung diseases in the UK in 2010–2019 - Francesca Gonnelli; Neva Eleangovan; Ursie Smith; Heath Heatley; Vidya Navarantam; Tamera J. Corte; David B. Price; Victoria Carter; Martina Bonifazi; Caitlin C. Fermoyle; Richard Hubbard (ERJ Open Research)
Background With the introduction of the antifibrotic drugs targeting progressive pulmonary fibroses, it becomes imperative to provide reliable contemporary estimates of the most common interstitial lung diseases. We aimed to provide contemporary estimates of the incidence and survival of idiopathic pulmonary fibrosis (IPF), hypersensitivity pneumonitis (HP) and connective tissue disease-associated interstitial lung disease (CTD-ILDs), and to compare their survival to that of the general population. To do this we have used data extracted from the Optimum Patient Care Research Database (OPCRD). Methods In this matched cohort study, we extracted incident cases of HP, CTD-ILD and IPF, and age and sex matched controls for each case, for the years 2010–2019. We calculated annual incidence rates and analysed incidence trends over time using segmented regression modelling. We estimated survival for cases and controls using the Kaplan–Meier model. Results We extracted data for 18 914 incident cases of interstitial lung diseases between 2010 and 2019 from the OPRCD. Incidence rates varied across the different diseases, with rates of 18.12, 7.96 and 2.63 per 100 000 person-years for IPF, CTD-ILD and HP, respectively. 5-year survival for IPF, CTD-ILD and HP was 40%, 54% and 66%, respectively, and this was generally ∼50% lower than that of the general population. Conclusion Our population-based study emphasises the considerable burden of interstitial lung diseases, with >20 000 new cases diagnosed each year in the UK, many of whom will be eligible for antifibrotic drugs.